Diagnosis and Treatment of Status Epilepticus in a Pediatric Renal Recipient. (5th January 2012) - Hongjun, Gao; Xiangdong, Luo; Taisheng, Liang; Shangguang, Lu; FangFang, Liang; Yu, Dong; Zhen, Tan; Zhen, Wu
Abstract : We elaborate on the retrospective analysis of clinical data on a patient afflicted with grand mal seizures following a kidney transplant. The 16-year-old female patient was hospitalized for chronic glomerulonephritis. She experienced an epileptic seizure and was treated with carbamazepine. Renal transplantation was performed; the function of the transplant kidney was normal. However, grand mal seizures, which required intravenous and luminal intramuscular diazepam injections for control, began on the fourth postoperative day and lasted for 3 days, occurring approximately 10 to 20 times per day. On the sixth day, the patient fell into a deep comatose state and developed the inability to move the right side of her body, hypomyotonia, type 1 respiratory failure, and a pulmonary infection. She was given a breathing machine to assist with respiration. At the same time, she was given protection from infection, tranquilization, treatment for dehydration and diuresis, supportive therapy for the right side of her body, and adjustment of her immunosuppressants. On the 12th postoperative day, the patient's consciousness gradually returned; on the 15th day, the breathing machine was removed with recovery of myodynamia; on the 27th day, she was fully cured with no neurological sequelae.